The Urgency of the "Lana Bango" Protection Law as a Regional Superior Product of Sangihe Islands Regency - Mercy Maria Magdalena Setlight (Journal of Law, Politic and Humanities, 2024)
Sangihe Islands Regency through the Decree of the Regent of the Sangihe Islands Number 143/510/Year 2019 stipulates "Lana Bango", as a Regional Superior Product which is an effort by the Sangihe Islands Regency Government to reactivate community culture in the manufacture of Sangihe local coconut oil which is currently produced in a more hygienic manner by several villages through Village-Owned Enterprises (Bumdes). For this reason, there needs to be a formal determination from policymakers based on the results and analysis of a research, so that legal urgency in this case can be applied. It becomes a significant problem when there are no new coconut plants that replace old coconuts that are cut down. The Sangihe Islands which is a small island, if there is only logging and there is no replanting, then the coconut plant will one day become extinct and this will result in processed coconut products in the form of local coconut oil "Lana Bango", which is the Regional Superior Product of the Sangihe Islands Regency will remain memories in the form of stories for posterity.